Kisana Glycolic Soap Product Marketing Management Strategy in Increasing Brand Awareness in the Indonesian Skincare Market - Prasasti Sutaningdyah (Journal of International Conference Proceedings, 2025)
This study aims to analyze the marketing management strategy of Kisana Glycolic Soap in increasing brand awareness in the Indonesian skincare market. The underlying phenomenon of this research is the increasing competition in the local skincare industry, which demands innovation in brand communication strategies to compete with global products. This research employed a qualitative approach with a case study method, allowing for an in-depth exploration of communication strategies and consumer perceptions of the brand. Data were collected through semi-structured interviews, participant observation, and digital documentation. The results indicate that Kisana's marketing strategy focuses on three main themes: (1) consumer education through informative content marketing, (2) consistent communication across digital platforms, and (3) collaboration with micro-influencers to build brand authenticity. Practically, Future research is recommended to explore the dynamics of consumer perception across age and cultural segments to broaden our understanding of the effectiveness of local brand communication in the digital era